Sea cucumbers in the Seychelles: effects of marine protected areas on high‐value species. Issue 3 (21st January 2013) - Cariglia, Nicoletta; Wilson, Shaun K.; Graham, Nicholas A. J.; Fisher, Rebecca; Robinson, Jan; Aumeeruddy, Riaz; Quatre, Rodney; Polunin, Nicholas V. C.
ABSTRACT In tropical regions all over the world, holothurian (sea cucumber) fisheries are an important source of income for local communities. Almost all fisheries targeting holothurians are considered fully exploited or in decline, and several fisheries have collapsed. This study examined the differences in abundance of commercially exploited and ecologically important coral reef holothurian species between long established marine protected areas (MPAs) and unprotected areas in the inner islands of the Seychelles. Over a period of 1 month, 21 sites across the inner islands of the Seychelles were surveyed, nine of which were within MPAs. The probability of observing holothurians in areas protected from fishing (~80%) was twice that in areas subjected to fishing. The probability of observing holothurians of high or medium commercial value in counts was 10‐fold greater inside rather than outside MPAs. Habitat was an important determinant of holothurian presence: occurrence of high and medium value holothurians was associated with rock and coral habitats. MPAs may help conserve high densities of holothurians of economic importance. Copyright © 2013 John Wiley & Sons, Ltd.